Analysis of water quality of natural touristic attractions located in the community of Cabeça de Boi, Itambé do Mato Dentro (MG) (Research, Society and Development, 2018)
Tourism activities can trigger positive and negative impacts in a community in the economic, social and environmental spheres. Among the negative impacts that tourism can cause, it is worth noting the deterioration of water quality, which may compromise its various uses, including for recreation purposes. Thus, this research aimed to analyze the water quality and bathing conditions of tourist attractions located in the community of Cabeça de Boi, Itambé do Mato Dentro (MG). The sample used in this research corresponded to the known attractions such as Lajeado, Poço and the Intancado, Maçã and Chuvisco waterfalls sampled between the months of March and August of 2016. Considering the conditions of bathing, among the water resources analyzed, it is worth noting that Chuvisco waterfall and Lajeado are the best options for performing recreation activities, while the well presents the worst conditions, given the presence of higher concentrations of Escherichia coli. Regarding the Water Quality Index, it was verified that the samples from Chuvisco waterfall presented better quality, corresponding to the "good" classification range. In general, in order to contribute to the development of sustainable tourism in the Cabeça de Boi community, it is necessary to focus on environmental education involving tourists and residents, as well as the continuous monitoring of the water quality of the attractions.